ASSESSMENT OF HAZARDOUS ENGINEERING-GEOLOGICAL AND HYDROGEOLOGICAL PROCESSES ON THE ALMATY CITY TERRITORY - Altynay E. Zhakyp; Vladimir M. Mirlas; Yergali S. Auelkhan (Известия Томского политехнического университета: Инжиниринг георесурсов, 2021)
The relevance of the research is caused by the need to study hazardous engineering-geological and hydrogeological processes developing on Almaty city territory that pose a threat to the life of urban residents and to industrial and civil building. In addition, the relevance of the research is caused by the need to assess the human economic activity impact on the geological environment state. Purpose: description and zoning of the Almaty city territory according to the type and modern state of development of hazardous geological processes and identification of the most hazardous areas potential, from the point of view of the development of hazardous geological processes for their detailed study; selection of an experimental site for assessing and prediction buildings underflooding development using a geofiltration models. Objects: landslides, landfalls, mudflow phenomena developing in the foothill sites; the groundwater level rising in the central part of the city in the sites of existing water intakes facilities; underflooding of certain sites in the northern part of the city. Methods: research and classification of hazardous geological processes developing in the Almaty city; systematization and analysis of the main factors of their occurrence and development on the territory, based on the results of earlier field investigations and published works; field research and mapping of the selected experimental site; creation of a database, including climatic, geological, hydrological, hydrogeological data; route survey of the experimental site, the groundwater level monitoring in observation wells; observations of the state of river flow and flood events. Results. On the territory of Almaty city, there are three main groups of hazardous geological processes associated with certain areas: 1 – landslides, landfalls, mudflows developing in the foothill areas of the city; 2 – groundwater level rising in central part of the city, where existing water intakes, leading to increase in the seismicity level; 3 – underflooding resulting from the deterioration of the natural drainage of territory due to the filling and planning of the existing depressions in the relief and the «кarasu» rivers. The assessment of the potential underflooding of the territory allowed us to class it as the first degree in terms of potential underflooding. The estimated period of the territory underflooding will be from 4 to 5 years. Taking into account the dynamics of the process of the territory underflooding, it is concluded about the necessity to create a geofiltration model for predictive assessment of the process development of buildings flooding on this territory.